(3JSdjI GdMRjf aj abO GdYGajI hGdCMHGH ef GdCbGQH hGdHfjfs - (3GdMSjfj, GdcGXej, oTnqHQ, GdeLdSj GdKGfj, YHO Gddg Hf eMeO QVG Bd THQ, J (B1242(3g`s ((3gGOj TjQ GdMSjfjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj bgQ YHGOg HGdehJ hGdafGA(B... (3hHYO(B...(3gPg JSdjI ddMRjf (B...s
(3BNQgG (B:s
(3ef Gddg GdJSdje aQjVI hYdjg GdfYeI ef Gddg GdTcQ(B... (3Gddge CUdM dfG OjffG hOfjGfG hBNQJfG(B...s
(3JHUQI GdYfhGf (B:s
(3JSdjI GdMRjf HabO GdCMHGH hGdHfjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, HQbe(B: 878s
(3GdPQjYI, HQbe(B: 878s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs